Odpowiedzi

2010-01-25T15:24:06+01:00
8(7-4y)-7(4y+1)+5(8y-1)=19
56-32y -28y -7 + 40y-5 = 19
44 -20y = 19
-20y = 19 - 44
-20y = -25 /: (-20)
y = 1,25

3(2x+1)-5(12x-7)+7(6x-1)=23
6x+3-60x+35+42x-7 = 23
-12x + 31 = 23
-12 x = 23 - 31
-12 x = -8 / :(-12)
x = 8/12 = 2/3
2010-01-25T15:25:40+01:00
56-32y-28y-7+40y-5=19
-20y=-25
y-1.25

6x+3-60x+35+42x-7=23
-12x=-8
x=2/3
  • Użytkownik Zadane
2010-01-25T15:29:15+01:00
8(7-4y)-7(4y+1)+5(8y-1)=19
56-32y-28y-7+40y-5=19
44-20y=19
-20y=-25
y=25/20=1 5/20= 1¼

3(2x+1)-5(12x-7)+7(6x-1)=23
6x+3-60x+35+42x-7=23
-12x+31=23
-12x=-8
x=8/12=2/3